The Impact of Emotional Intelligence and Self-Efficacy on Employee Performance Through Organizational Citizenship Behavior: A Case Study of PDAM Tirta Jati Cirebon - Fitriani, Suci; Zuhriyah, Syifa; Maryam, Siti (International Journal of Business, Economics, and Social Development, 2025)
This study aims to analyze the effect of emotional intelligence and self-efficacy on employee performance of PDAM Tirta Jati Cirebon Regency, with Organizational Citizenship Behavior (OCB) as a mediating variable. In the midst of increasingly fierce global competition, human resource development is the key for companies to stay ahead. Employee performance is influenced by internal factors such as emotional intelligence and self-efficacy, as well as external factors such as OCB. This research uses a quantitative approach with a causal associative method. Data were collected through questionnaires with 180 respondents and employee interviews selected by simple random sampling from a total of 325 employees. The results showed that emotional intelligence and self-efficacy have a significant effect on employee performance, and OCB acts as a significant mediating variable. Developing emotional intelligence and increasing self-efficacy are important to improve OCB, which in turn will contribute to overall employee performance.